Effect of pH on phenol biosorption by marine seaweeds - Navarro A.E. (2008)
The present work was financed by the project 152-2006-CONCYTEC-OAJ granted by the National Council of Science and Technology to B.L. A.N. thank the H. McCracken doctoral scholarship at the New York University. The authors would also like to thank the Department of Chemistry of the Faculty of Sciences and Philosophy of the Cayetano Heredia University, the Section of Chemistry of the Department of Sciences of the Pontifical Catholic University of Peru and Norma Cuizano, Todd Kelly, Richard Buran and Paul Henkel for their contributions and critical comments concerning this research.